Favipiravir for Treatment of Outpatients With Asymptomatic or Uncomplicated Coronavirus Disease 2019: A Double-Blind, Randomized, Placebo-Controlled, Phase 2 Trial. (21st April 2022) - Holubar, Marisa; Subramanian, Aruna; Purington, Natasha; Hedlin, Haley; Bunning, Bryan; Walter, Katharine S; Bonilla, Hector; Boumis, Athanasia; Chen, Michael; Clinton, Kimberly; Dewhurst, Liisa; Epstein, Carol; et al.
Abstract: Background: Favipiravir, an oral, RNA-dependent RNA polymerase inhibitor, has in vitro activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Despite limited data, favipiravir is administered to patients with coronavirus disease 2019 (COVID-19) in several countries. Methods: We conducted a phase 2, double-blind, randomized controlled outpatient trial of favipiravir in asymptomatic or mildly symptomatic adults with a positive SARS-CoV-2 reverse-transcription polymerase chain reaction assay (RT-PCR) within 72 hours of enrollment. Participants were randomized to receive placebo or favipiravir (1800 mg twice daily [BID] day 1, 800 mg BID days 2–10). The primary outcome was SARS-CoV-2 shedding cessation in a modified intention-to-treat (mITT) cohort of participants with positive enrollment RT-PCRs. Using SARS-CoV-2 amplicon-based sequencing, we assessed favipiravir's impact on mutagenesis. Results: We randomized 149 participants with 116 included in the mITT cohort. The participants' mean age was 43 years (standard deviation, 12.5 years) and 57 (49%) were women. We found no difference in time to shedding cessation overall (hazard ratio [HR], 0.76 favoring placebo [95% confidence interval CI, .48–1.20]) or in subgroups (age, sex, high-risk comorbidities, seropositivity, or symptom duration at enrollment). We detected no difference in time to symptom resolution (initial: HR, 0.84 [95% CI, .54–1.29]; sustained: HR, 0.87 [95% CI, .52–1.45]) and no difference in transition mutation accumulation in the viral genome during treatment. Conclusions: Our data do not support favipiravir at commonly used doses in outpatients with uncomplicated COVID-19. Further research is needed to ascertain if higher favipiravir doses are effective and safe for patients with COVID-19. Clinical Trials Registration: NCT04346628. Abstract : In this phase 2, double-blind, randomized controlled outpatient trial of favipiravir in patients with asymptomatic or uncomplicated COVID-19, we found no difference in time to shedding cessation or time to symptom resolution by treatment arm.